Konstruksi Isu Lingkungan di Media Indonesia - Serin Himatus Soraya; Sri Mulyani (Bahasa Indonesia, 2025)
This study aims to analyze how online media in Indonesia construct environmental issues through different perspectives of values ​​and ideologies. The two media outlets studied are NU Online, a representative of Islamic da'wah-based media, and Kumparan.com, a representative of general media based on digital journalism. This study uses Agenda Setting theory (McCombs & Shaw, 1972) to explore two levels of analysis: issue salience (the determination of the issue agenda) and attribute salience (the formation of meaning and values). The method used is qualitative content analysis with a descriptive-comparative approach to ten environmental articles published between September and October 2025. The results show that NU Online frames environmental issues within an Islamic ecotheological framework, emphasizing the values ​​of amanah (trust), khalifah (vicegerent), mizan (property), and ihsan (goodness) as the moral basis for preserving nature. Meanwhile, Kumparan.com emphasizes a technocratic and collaborative approach, addressing ESG issues, SDGs, and green innovation as a sustainable development strategy. Both media play a role in shaping public ecological awareness, but with different value orientations: spirituality in Islamic media and rationality in mainstream media. This research contributes to strengthening the media's role in building ethical, reflective, and sustainable public ecological awareness in Indonesia.